Pancreas-specific plasma amylase for assessment and diagnosis of chronic pancreatitis: New insights on an old topic. Issue 7 (August 2019) - Olesen, Søren Schou; Krarup, Henrik; Poulsen, Jakob Lykke; Christensen, Jeppe Hagstrup; Sheel, Andrea Rhiannon Glynne; Sutton, Robert; Greenhalf, William; Halloran, Christopher; Drewes, Asbjørn Mohr
Background: Pancreatic function testing and imaging are used to inform the diagnosis of chronic pancreatitis, but most of these methods are time- and cost-consuming or lack diagnostic accuracy. Objective: We investigated the utility of pancreas-specific plasma amylase for assessment and diagnosis of chronic pancreatitis. Design: This was a prospective study of 121 consecutive patients with chronic pancreatitis and a reference population of 94 healthy controls. Pancreas-specific plasma amylase level was determined and analysed for its association with exocrine pancreatic insufficiency, diabetes and other clinical variables. Receiver operating characteristic curve analyses were performed to determine the diagnostic utility of plasma amylase for diagnosing chronic pancreatitis and to study associations with disease severity. The findings were validated in a further cohort of 57 patients with chronic pancreatitis. Results: Significant and independent associations between plasma amylase level and duration of chronic pancreatitis as well as the presence of exocrine pancreatic insufficiency and diabetes were observed (all p  < 0.001). An amylase level below 17.3 U/l had a high specificity (94%) and moderate sensitivity (59%) for the diagnosis of chronic pancreatitis. Diagnostic performance was influenced by disease stage with the best performance observed for advanced disease. The findings were replicated in the validation cohort. Conclusion: Pancreas-specific plasma amylase may provide a clinically useful mean for assessment and diagnosis of chronic pancreatitis.